Mathematical Study Of Weighted Generalized Exponential Distribution (Journal of the College of Basic Education, 2022)
This paper deals with studying a weighted Generalized Exponential distribution with the known shape parameter α=2 and scale parameter λ>0 and driving it's probability distribution function, cumulative distribution function , reliability function. Also driving the moment generating function and other moments.Also we driving the estimator for λ by MLE and MOM.